Assessment of small ruminant welfare in Addis Ababa Municipal Abattoir Enterprise, Ethiopia - Bekele, T.; Szonyi, Barbara (International Livestock Research Institute, 2014)
A cross sectional study was conducted with the objective of assessing the welfare of small ruminants at the Addis Ababa Municipal Abattoir Enterprise (AAMAE) in Addis Ababa, Ethiopia. A total of 384 small ruminants (192 sheep and 192 goats) were subjected to clinical examination and behavioral observation from September 2014 to December 2014. In the lairage, the behavior of 57 animal handlers was observed. In addition, one abattoir worker was interviewed to get information on market origin, transportation of shoats from market to abattoir and handling of small ruminants in the lairage. During clinical examination, dirty skin, poor body condition, and respiratory disorders were the most common abnormalities. Fighting (5%) and running (5%) were the most frequently observed aggressive behaviors in both sheep and goats at the lairage. The jumping behavior was never seen in sheep but was observed in 4 (2%) goats. The most frequently expressed stress related behaviors were panting (16%) and idling (11%). Commonly observed resistance behavior included refusing to move (17%), reversing (11%), balking (3%) and resistance to being pulled (9%). Falls (8%) were frequently observed followed by slipping severely (3%). Beating of body (88%) was the most frequently observed abusive behavior by the small ruminant handlers followed by pushing (58%) and pulling (50%). One abattoir worker reported poor overall transport conditions for the animals, including long transport times, lack of feed, water and rest during transport, and overcrowding. Problems in lairage design were also noted. This was the first study to assess small ruminant welfare at a major abattoir in Ethiopia. The study revealed high levels of stress and resistance behavior in the animals at the lairage. Poor handling of animals and abusive behavior by handlers, particularly beating, was very common. In line with this finding, it is recommended that education on animal welfare be included in the training of abattoir workers and animal handlers.